Effect of crystal silica on thermal conductivity of elastic encapsulant. (August 2014) - Shen, Mingxia; Han, Yongqin; Duan, Pengpeng
A crystal silica was intermingled with an elastic ethylene-vinyl acetate polymer to fabricate an encapsulant and improve its thermal conductivity. The encapsulant showed not only an improved thermal conductivity and adhesiveness but also good thermal stability and tenacity. Its thermal conductivity with various sizes, dosage, and surface properties of silica (SiO2 ) was investigated using laser scattering method. The tenacity and adhesion properties were evaluated using dynamic viscoelasticity and peel strength, respectively. The integrated properties of the encapsulant were obtained while SiO2 reached to 80 wt portions in composite. Thermal conductivity of the composite was less dependent on the surface properties of SiO2 .